Opportunistic CT Screening for Osteoporosis in Patients With Pelvic and Acetabular Trauma: Technique and Potential Clinical Impact. Issue 8 (August 2018) - Donohue, David; Decker, Summer; Ford, Jonathan; Foley, Robert; Dunbar, Kirstin; Kumm, Todd; Achors, Kyle; Mir, Hassan
Abstract : Objectives: To present a technique for the use of computed tomography (CT) scans in opportunistic screening for osteoporosis in patients with pelvic and acetabular fractures and to quantify the potential clinical impact in a geriatric trauma population. Design: Retrospective cohort study. Setting: Level 1 trauma center. Patients: A total of 335 patients older than 60 years of age who presented to a Level 1 trauma center with a diagnosis of pelvic or acetabular fracture and were evaluated with a CT scan between the years 2010 and 2016. A subset of 255 patients were evaluated with a dual-energy x-ray absorptiometry scan within 6 months of the CT scan. Intervention: Measurement of Hounsfield units (HU) was performed at the midpoint of the femoral neck using a standardized, ovoid section, followed by Livewire measurement. Application of this technique retrospectively to a population of geriatric patients with pelvic or acetabular fractures. Main Outcome Measurements: (1) HUs were measured in a cross section at the midpoint of the femoral neck and, discriminant function analysis was used to establish thresholds for normal bone mineral density, osteopenia, and osteoporosis. (2) Change in the number of diagnoses of osteoporosis after application of the protocol the geriatric trauma cohort. Results: Patients with osteopenia were identified correctly 67.5% of the time (14.3% were incorrectly grouped as normal, and 18.3% were grouped as having osteopenia). Patients with osteoporosis were identified correctly 88.9% of the time (the remaining 11.1% were assigned to osteopenic). The results of discriminant function analysis were used to establish CT thresholds for osteopenia (345 HUs) and osteoporosis (262 HUs). Conclusion: CT imaging obtained for pelvic and acetabular fractures can identify patients with osteoporosis without additional radiation exposure or cost. The fitted ovoid region of interest is a standard feature in most CT scan platforms and is quite simple to perform. Level of Evidence: Diagnostic Level II. See Instructions for Authors for a complete description of levels of evidence.